Investigating gas/solid separation using a novel compact inline separator - White, Tyrone (Cranfield University, 1999)
Identified as an important issue for marginal fields, the removal of sand from hydrocarbon fluids has been investigated. A review of existing sand separation equipment has recognized a need for a new separator which will satisfy the design and performance requirements necessary for protecting offshore processing equipment. This thesis details the work and analysis undertaken which has contributed towards the design and development of a new offshore gas/solid separator. A critique of different separation techniques has identified axial flow cyclone (AFC) separators as a suitable separator design for offshore desanding applications. After reviewing existing models which simulate the performance of AFC separators a simple classification table has been developed. Using the conclusions of this review as a starting platform, a methodology for developing a new computational fluid dynamics (CFD) performance model for the new separator was proposed. Experimental work undertaken at the CALtec laboratories and the BG plc (formerly British Gas Research and Technology) Low Thornley test facilities are presented. The results obtained have been used to analysis the performance of difference separator internal designs. In addition, the results have been used to evaluate the robustness of existing AFC performance models and validate the new CFD model. For the investigated operational duties, the new CFD model has been shown to consistently under-predict the collection efficiency, whereas the other AFC models over-predict. From a design point of view, a model which under-predicts the overall collection efficiency will result in the over-design of the separator for a particular operating duty. Therefore, the use of such a model will ensure the design of a separator which will offer greater than expected levels of protection of downstream equipment from erosion wear.